Coexistence Of Plasmid-Mediated mcr-1 And bla(NDM-4) Genes In A Klebsiella pneumoniae Clinical Strain In Vietnam - Le, Lien (Infect Drug Resist, 2019)
In this study, we characterized the first clinical Klebsiella pneumoniae strain co- harboring mcr-1 and bla(NDM-4) genes in Vietnam, which was recovered from a patient admitted to hospital in 2015. This strain demonstrated nonsusceptible to all tested antibiotics, including last-line antibiotics such as carbapenems (MICs ≥128 μg/mL) and colistin (MIC =32 μg/mL), except tigecycline (MIC =1 μg/mL). Whole-genome analysis using both MinION and MiSeq data revealed that the strain carried 29 resistance genes. Particularly, mcr-1 and bla(NDM-4) genes were carried by different self-conjugative plasmids and able to be transferred to a recipient by conjugation. The colistin resistance of this strain was conferred by mcr-1 and additional chromosomal resistance determinants. Eight amino acid substitutions found in PmrA, PmrB, PmrC, PmrI, and PmrJ, all proteins that are involved in lipopolysaccharide modifications, may be associated with chromosomal colistin resistance. The accumulation of multiple antibiotic resistance mechanisms in this clinical isolate raises alarm on potential spread of extensively drug-resistant K. pneumoniae in healthcare settings.